The Level of Community about Leptospirosis in Sukaramai, Medan, Indonesia - Dr. dr. Nurfadly, MKT. (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
iBackground: Leptospirosis is a zoonotic disease caused by Leptospira interogans. Leptospirosis in Indonesia has a fairly high incidence of third-order m01tality in the world. A person's knowledge of a disease will affect one's assessment of the disease. Poor knowledge of a disease is likely to be able to reduce the incidence of the disease. Objective: To determine the level of community knowledge about Leptospirosis in Sukaramai , Medan, Indonesia. Method: This research type is descri ·ve with the crosssectional design. Samples of research with simple random sampling technique with the number of 81 people located in Sukaramai, Medan. The instrument of this study used a questi01